STRESS INTERACTION BETWEEN THRUST FAULTS ALONG THE SW HELLENIC ARC (GREECE) - Messini, A.; Papadimitriou, E. E.; Karakostas, V. G.; Baskoutas, I. (Bulletin of the Geological Society of Greece, 2007)
The occurrence of strong earthquakes (M>6.3) and the evolution of the stress field along the southwestern part of the Hellenic arc since 1959 are examined by the calculation of Coulomb stress changes. The study area is characterized by low angle thrust faults and high seismicity as being part of the subduction interface. Coulomb stress changes were calculated assuming that earthquakes can be modeled as static dislocations in an elastic half-space, considering the co-seismic slip during strong events and the slow tectonic stress build-up along major fault segments due to the movements of the tectonic plates. The ruptures are modeled taking into account the strike, dip, and rake appropriate to each event examined. It is evaluated whether the stress changes brought a given earthquake closer to, or farther away from, failure. It was found that the majority of the events (strong and smaller) are located in stress enhanced areas.